Hubungan pengetahuan ibu dengan tindakan manajemen swamedikasi pada anak balita di Desa Ketapang Dua Aceh Timur. - Shufyani, Fahma; Siregar, Syati Manaharawan; Dominica, Dwi (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: Self-medication is something that is often practiced by the Indonesian community as a way to take care of themselves when they are sick. Taking and consuming medication without advice from a healthcare professional, whether for diagnosis, prescription, or health supervision, is called self-medication. Self-medication can provide significant benefits to the government in maintaining national health if done correctly. Self-medication can assist healthcare professionals, reduce the time spent waiting for a doctor's diagnosis, and save money, especially in developing countries, because healthcare professionals will be more focused on more serious and critical health conditions. Objective: This study aims to determine mothers' knowledge about self-medication for fever and to understand the self-medication actions taken by mothers, as well as to examine the relationship between mothers' knowledge and their self-medication actions for fever in toddlers in Ketapang Dua Village, East Aceh. Method: This study uses a quantitative method of a descriptive-analytical nature with a cross-sectional design. The sampling technique used purposive sampling. Data were analyzed using the Chi Square test. Data collection was conducted in July 2024. The research population is the knowledge of mothers regarding self-medication management for toddlers in Ketapang Dua Village, East Aceh. The sample of this study consists of 40 respondents. Results: from this study indicate that 35% of mothers have a fairly good level of knowledge about self-medication for fever. Self-medication for fever in toddlers shows that around 47.5% have taken appropriate actions. There is a significant relationship between maternal knowledge and self-medication actions for fever in toddlers in Ketapang Dua Village, East Aceh, with a p-value of 0.026 < 0.05. It can be concluded that the presence of maternal knowledge regarding self-medication for fever in toddlers in Ketapang Dua Village, East Aceh, is classified as quite good. The conclusion: of this study is that the frequency distribution of maternal knowledge shows that some have fairly good knowledge, with 14 respondents (35.0%) and respondents with less adequate knowledge amounting to 21 respondents (65.5%). The frequency distribution of fever self-medication actions shows that some mothers provided appropriate self-medication actions, with 19 respondents (47.5%) doing so, while 21 respondents (52.5%) provided less appropriate self-medication actions. There is a significant relationship between maternal knowledge and self-medication practices for fever in toddlers in Ketapang Dua village, East Aceh, with a p-value of 0.026 > 0.05.